The carbon source influences the energetic efficiency of the respiratory chain of N2-fixing Acetobacter diazotrophicus - Luna, María Flavia (2000)
Acetobacter diazotrophicus is a diazotrophic bacterium that colonizes sugarcane tissues. Glucose is oxidized to gluconate in the periplasm prior to uptake and metabolism. A membrane-bound glucose dehydrogenase quinoenzyme [which contains pyrroloquinoline quinone (PQQ) as the prosthetic group] is involved in that oxidation. Gluconate is oxidized further via the hexose monophosphate pathway and tricarboxylic acid cycle. A. diazotrophicus PAL3 was grown in a chemostat with atmospheric nitrogen as the sole N source provided that the dissolved oxygen was maintained at 1.0–2.0% air saturation. The biomass yields of A. diazotrophicus growing with glucose or gluconate with fixed N were very low compared with other heterotrophic bacteria. The biomass yields under N-fixing conditions were more than 30% less than with ammonium as the N source using gluconate as the carbon source but, surprisingly, were only about 14% less with glucose. The following scheme for the metabolism of A. diazotrophicus through the different pathways emerged: (1) the respiratory chain of this organism had a different efficiency of ATP production in the respiratory chain (P:O ratio) under different culture conditions; and (2) N fixation was one (but not the sole) condition under which a higher P:O ratio was observed. The other condition appears to be the expression of an active PQQ-linked glucose dehydrogenase.